Real Story in Reel Life; Ethnographic Description of Contemporary Nepalese Films (Triyuga Academic Journal, 2021)
The main purpose of this study is to investigate the ethnographic picture of the five different social films of Nepal. This study looks at the representation of social life in contemporary five social films directed by men and women till 2018. Based on background quantitative data as well as a qualitative content analysis, this paper found that portrayals of film life juxtapose to real life. The focus of the films, story of the films, message of the films were analyzed anthropologically as the life, character, story that are found in films are the part or the representation of our social life. The messages that are passes from the film are the product of that particular society. It is the representative expression of all social life, aspiration, problems that are found all over the country. Mainly, different contents in films were found though same territory, people, but different is the message, time, characters, story, etc. found the content. Their films of different genres were found. Five different films or reel contents were analyzed and found different stories, role, but represent the real life of different era or time presented differently. That’s why films are also the means of study of the society, culture and anything else associated with human life anthropologically because films are the part and product of the particular society and culture.